2006
DOI: 10.1016/j.bbadis.2005.11.008
|View full text |Cite
|
Sign up to set email alerts
|

In vivo contribution of Class III alcohol dehydrogenase (ADH3) to alcohol metabolism through activation by cytoplasmic solution hydrophobicity

Abstract: Alcohol metabolism in vivo cannot be explained solely by the action of the classical alcohol dehydrogenase, Class I ADH (ADH1). Over the past three decades, attempts to identify the metabolizing enzymes responsible for the ADH1-independent pathway have focused on the microsomal ethanol oxidizing system (MEOS) and catalase, but have failed to clarify their roles in systemic alcohol metabolism. In this study, we used Adh3-null mutant mice to demonstrate that Class III ADH (ADH3), a ubiquitous enzyme of ancient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…Increased expression of pgls could contribute to decreased lifetime of 6-phosphogluconolactone, its highly reactive and potentially toxic substrate. Alcohol dehydrogenase class-3 ( adh3 ) , also induced, constitutes the primary defence mechanism against formaldehyde damage and may also indirectly mediate protection of proteins against oxidation [71]. Gene encoding heme oxygenase 1 ( ho-1 ) that has important antioxidant and cytoprotective activities was the most highly induced gene by dietary GLs in muscle (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Increased expression of pgls could contribute to decreased lifetime of 6-phosphogluconolactone, its highly reactive and potentially toxic substrate. Alcohol dehydrogenase class-3 ( adh3 ) , also induced, constitutes the primary defence mechanism against formaldehyde damage and may also indirectly mediate protection of proteins against oxidation [71]. Gene encoding heme oxygenase 1 ( ho-1 ) that has important antioxidant and cytoprotective activities was the most highly induced gene by dietary GLs in muscle (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…This pyrazole-insensitive pathway has a greater metabolic role when the level of blood alcohol is high or when the intake of alcohol is chronic [2–7]. Recently, we used ADH1-null mice to show that ADH1 accounts for about 70% of systemic alcohol metabolism [25,26], which means that the non-ADH1 pathway accounts for the remaining 30%. Regarding the identity of the main enzyme responsible for this pathway, a heated scientific debate has continued for three decades over whether it is catalase [1012] or MEOS, which is mainly composed of CYP2E1 [2–9].…”
Section: Historical Debate On the Identification Of Enzyme(s) In The mentioning
confidence: 99%
“…Recently, we used ADH3-null mutant mice to demonstrate that the contribution of ADH3 to alcohol metabolism in vivo increases dose-dependently [25]. …”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that ethanol-mediated expression of RANTES (regulated upon activation normal T cell expressed and secreted) and endothelin-1 was dose-dependent (25-100 mM) with optimal expression at 100 mM ethanol (38,39); thus, we utilized this dose of ethanol for studies described herein. Although this concentration of alcohol (0.46%) may seem physiologically high, studies (40) show that the metabolism of ethanol increases to accommodate increased alcohol intake in chronic alcoholics. Treatment of C-rKCs with ethanol (100 mM) showed 3-and 7-fold increase in HO-1 mRNA expression at 12 and 24 h, respectively.…”
Section: Ethanol Augments Ho-1 and Hif-1␣ Mrna Expression Inmentioning
confidence: 99%